2009
DOI: 10.1111/j.1747-0285.2009.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

Active Site Ring‐Opening of a Thiirane Moiety and Picomolar Inhibition of Gelatinases

Abstract: Abstract(±)-2-[(4-Phenoxyphenylsulfonyl)methyl]thiirane 1 is a potent and selective mechanism-based inhibitor of the gelatinase sub-class of the zinc-dependent matrix metalloproteinase (MMP) family. Inhibitor 1 has excellent activity in in vivo models of gelatinase-dependent disease. We demonstrate that the mechanism of inhibition is a rate-limiting gelatinase-catalyzed thiolate generation via deprotonation adjacent to the thiirane, with concomitant thiirane opening. A corollary to this mechanism is the predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
89
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(94 citation statements)
references
References 52 publications
5
89
0
Order By: Relevance
“…As reported earlier in our mechanistic studies of the thiirane-type gelatinase inhibitors, slow-binding behavior is a hallmark of the mechanism of action of this type of inhibitors. 12,19,20 We showed that inhibitor 1 exhibited slow-binding inhibition of gelatinases, which we proposed to be at the root of selectivity. 12 As proposed earlier, gelatinases deprotonate R to the aromatic sulfone moiety, which leads to the opening of the thiirane ring and the release of the thiolate.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…As reported earlier in our mechanistic studies of the thiirane-type gelatinase inhibitors, slow-binding behavior is a hallmark of the mechanism of action of this type of inhibitors. 12,19,20 We showed that inhibitor 1 exhibited slow-binding inhibition of gelatinases, which we proposed to be at the root of selectivity. 12 As proposed earlier, gelatinases deprotonate R to the aromatic sulfone moiety, which leads to the opening of the thiirane ring and the release of the thiolate.…”
mentioning
confidence: 99%
“…12,19,20 We showed that inhibitor 1 exhibited slow-binding inhibition of gelatinases, which we proposed to be at the root of selectivity. 12 As proposed earlier, gelatinases deprotonate R to the aromatic sulfone moiety, which leads to the opening of the thiirane ring and the release of the thiolate. Hence, the thiirane behaves as a caged thiolate, which becomes available within the active site of gelatinases.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…6 The compounds of the thiirane class have a unique mechanism of action, involving ring-opening of the thiirane ring at the active site of gelatinases and generation of the thiolate, which is a picomolar and tight-binding inhibitor. 7 The blood-brain barrier (BBB) forms a physical separation between circulating blood and the brain parenchyma and consists of tight junctions around endothelial cells surrounded by basement membrane. The BBB prevents pathogens and large hydrophilic molecules from entering the brain, while allowing transport of substances needed by the central nervous system (CNS) such as glucose, fatty acids, and vitamins.…”
mentioning
confidence: 99%